The relationship between leadership and employee engagement in an automotive original equipment manufacturer in South Africa - Slater, Bronwyn Lereen (Rhodes University, Faculty of Commerce, Department of Management)
The manufacturing industry is one of the greatest contributors to the South African economy. Owing to a competitive and complex automotive climate, it is suggested that only a few automotive manufacturing organisations will remain viable in the coming years, without the optimal reliance on human capital resources to navigate an unpredictable and unfolding landscape. In securing a sustainable future, the engagement of these human capital resources is necessitated. This competitive landscape has resulted in the call for adaptive and flexible leadership. Leadership behaviour is categorised into three streams, namely, transformational leadership, transactional leadership, and non-leadership, which is referred to as laissez-faire leadership. Employee engagement is defined as the extent to which an employee is committed to, and involved in, their operational function and the organisation, whilst portraying a willingness to perform and contribute beyond that which is expected of them. The purpose of this research was to explore the relationship between leadership and employee engagement in an Original Equipment Manufacturer (OEM) in South Africa. This OEM operates in the Eastern Cape and Gauteng Provinces of South Africa. Globally, the OEM launched a leadership journey to facilitate a shared value system that supported a vision towards organisational success, by focusing on transformed ways of working and acting, as a global collective team. The outcome of this desired journey yielded eight Leadership Principles. These Leadership Principles are referred to, and included in the research study, to gain a more robust internal perspective of the leadership behaviours that are most advocated within the OEM, in relation to employee engagement. The objective of this research therefore was to establish the relationship between leadership and employee engagement in the respective OEM, by investigating the impact of transformational leadership and transactional leadership on employee engagement. A triangulation approach was adopted to analyse the data, using a combination of qualitative and quantitative research methodologies. The result when testing the reliability coefficient scores of the leadership instrument described a poor measure for transactional leadership, and a good measure for transformational leadership. Therefore, the results that stemmed from the statistical analysis in relation to transactional leadership could not be trusted. However, in the context of this research, it was found that there is a statistically significant relationship between transformational leadership and employee engagement. Whilst utilising the qualitative research methodology, it was found that there is a limited definition-based relationship between transactional leadership and the eight Leadership Principles. However, there is a definition-based relationship between the Leadership Principles and transformational leadership, owing to similarities found in the definition descriptions between at least six of the eight Leadership Principles. In the investigation of whether there is a definition-based relationship between the Leadership Principles and employee engagement, it was found that a limited definition-based relationship between the eight Leadership Principles and engagement existed. The research therefore met its objectives in determining a relationship between leadership and employee engagement in an Original Equipment Manufacturer in South Africa.
Keywords: Leadership; Transactional leadership; Transformational leadership; Employee engagement; Industrial relations; Automobile industry and trade -- South Africa